Comparative Study of the Work Engagement of Interns and Secondary School Teachers - Aouani, Hajer; Amara, Sofiene (Advances in Social Sciences Research Journal, 2024)
Background: Professional engagement is a complex process and likely varies depending on the individual’s personality and characteristics such as years of experience. There are conflicting results regarding the effect of professional engagement and its impact on work performance among physical education teachers and interns. Our study aims to examine the relationship between work engagement among physical education teachers and interns. Objectives: In this study, we compared work engagement between interns and physical education teachers. Methods: Two hundred fifty individuals (130 young interns, 120 qualified teachers) participated in this study. The teachers were classified based on their years of experience (1-2 years and 2-5 years). All participants completed the questionnaire translated and adapted by Loadhal and Kejner (1965), readapted by Alem, Bujold, et Bertrand, 2003 to evaluate the parameters of engagement. Results: Interns had significantly higher values in all dimensions of work engagement overall (all P < 0.001). Interns are more involved and motivated in their work, leading to better professional engagement overall. Comparison based on years of experience revealed that as the number of years increases, work engagement decreases among physical education teachers. Conclusions: Based on the results from our current study, we conclude that teacher’s professional commitment decreases over time.